Moisture content and mechanical properties reduction of hard capsules upon prolong drying process - Mohd Aiman, Hamdan; Nur Hikmah, Sulaiman; Khairatun Najwa, Mohd Amin; Fatmawati, Adam (IOP Publishing, 2021)
Drying is a traditional preservation method to control the properties and quality of pharmaceutical product such as hard capsule. In this study, carrageenan and nanocellulose (NC) solution were mixed with crosslinker and toughening agents in the formulation solution and dipped for hard capsule formation. The dipping bar was dried at different drying times from 40-60 minutes in an oven. The properties of carrageenan hard capsule were compared with commercial hard capsule materials which were gelatine and hydroxypropyl methylcellulose (HPMC). Prolong drying time decreased the moisture content and hydroxyl group absorbance of carrageenan hard capsule up to 20 % and 2%, respectively. The mechanical properties of the hard capsule sample reduced about 19.2 % due to reduction of intermolecular interaction between carrageenan, crosslinker and NC. Increment drying time leads to tissue shrinkage in carrageenan hard capsule thus collapse the biocomposite structure and mechanical properties. Gelatine and HPMC hard capsules had lower moisture content and higher mechanical strength and thermal properties as compared to carrageenan hard capsule. As the drying time increase, case hardening phenomena collapses the structure and change the structure chain in the biocomposite.